Incidence of ecto-and endo-parasitic fauna in small wild ruminants from North Eastern region of India - Patra, Gautam; Efimova, M. A.; Sahara, Ana; Borthakur, Sonjoy Kumar; Ghosh, Subhamoy; Behera, Parthasarathi; Polley, Shamik; Debbarma, Apurba (Taylor & Francis, 2022)
The present study reports the prevalence of ecto- and endo- parasites in small wild ruminants from various NE region of India. A total of 565 wild small ruminants in captivity were examined between April 2018 to March 2019 without causing harm to them. Faecal samples were examined microscopically for detection of different Gastrointestinal (GI) parasites. Animals were also inspected visually for any ectoparasitic infestation and skin scrapping examination was also performed from suspected skin lesion for mite infestation. Overall seven species of endoparasites including three nematodes, two trematodes, one cestode and one protozoan parasite were recorded. The overall prevalence of GI parasites was 28.36%. Prevalence of Strongyle infection was found highest (11.5%) followed by infection with Moniezia spp (4.6%), Paramphistomum sp. (3.53%), Strongyloides spp (2.12%), Trichuris spp (1.77%) and Eurytrema sp. (1.59%) and Eimeria spp (3.25%), A significant difference was observed in wet season as compared to dry season. Similarly, a correlation was observed between sex and age. Female and young animals were more commonly infected than males and older animals. Among ectoparasites, we recorded three genera of hard ticks namely, Boophilus sp., Rhipicephalus sp. and Haemaphysalis sp. and one genius of mite belonging to the genus Psoroptes. The study clearly indicated that season, sex and age and other epidemiological factors play a significant role in parasitism in small wild ruminants. The possibility of cross transmission of parasites between livestock and wild life in NE region of India should deserve attention.